SPACE BIOLOGI EXITING KNOWLEDGE AND PROBLEMS x) - R. C VON SORSTEL (Research Center for Biology-Indonesian Institute of Sciences, 1968)
Space research can always be justified simply on the basis of the knowladge we expert to gain on the nature of the universe.The knowladge gained will be Principally in the fields of astrophysies, meteorology ,geology, and biology.The field of biology in space research can be separated into three categories: interaction of living material with the space enviroment the search for extraterestrial life, and interstellar communication